A screen of apoptosis and senescence regulatory genes for life span effects when over-expressed in Drosophila - Shen, Jie (Impact Journals LLC, 2009)
Conditional expression of transgenes in Drosophila was produced using the Geneswitch system, wherein feeding the drug RU486/Mifepristone activates the artificial transcription factor Geneswitch. Geneswitch was expressed using the Actin5C promoter and this was found to yield conditional, tissue-general expression of a target transgene (UAS-GFP) in both larvae and adult flies. Nervous system-specific (Elav-GS) and fat body-specific Geneswitch drivers were also characterized using UAS-GFP. Fourteen genes implicated in growth, apoptosis and senescence regulatory pathways were over-expressed in adult flies or during larval development, and assayed for effects on adult fly life span. Over-expression of a dominant p53 allele (p53-259H) in adult flies using the ubiquitous driver produced increased life span in females but not males, consistent with previous studies. Both wingless and Ras activated form transgenes were lethal when expressed in larvae, and reduced life span when expressed in adults, consistent with results from other model systems indicating that the wingless and Ras pathways can promote senescence. Over-expression of the caspase inhibitor baculovirus p35 during larval development reduced the mean life span of male and female adults, and also produced a subset of females with increased life span. These experiments suggest that baculovirus p35 and the wingless and Ras pathways can have sex-specific and developmental stage-specific effects on adult Drosophila life span, and these reagents should be useful for the further analysis of the role of these conserved pathways in aging.